2018
DOI: 10.1590/s1984-296120180030
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Capillaria sp. in the liver of sheep (Ovis aries ) in a slaughterhouse in the state of Acre, Brazil

Abstract: Although sheep farming has grown in the state of Acre over the past four decades, little is known about occurrences of helminthiases in the herds of this region. The objective of the study was to assess the occurrences of non-intestinal helminthiasis among sheep slaughtered in Rio Branco. A total of 110 sheep livers were inspected from two slaughter batches (july 2014 and march 2015) in a slaughterhouse in Rio Branco. Livers with macroscopic lesions were photographed and were then subjected to histopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Calodium hepaticum ), is a globally distributed zoonotic parasite which uses rodents as main hosts, and while it is known to cause infection in over 180 mammalian species, a recent review of hosts did not include domesticated sheep ( 26 ). However, a recent study of Capillaria in Brazil identified two cases which were possibly caused by C. hepatica ( 115 ).…”
Section: Supplementary Resultsmentioning
confidence: 99%
“…Calodium hepaticum ), is a globally distributed zoonotic parasite which uses rodents as main hosts, and while it is known to cause infection in over 180 mammalian species, a recent review of hosts did not include domesticated sheep ( 26 ). However, a recent study of Capillaria in Brazil identified two cases which were possibly caused by C. hepatica ( 115 ).…”
Section: Supplementary Resultsmentioning
confidence: 99%